Outcome following open and endovascular intervention for carotid stump syndrome. (18th June 2018) - Dulai, Makinderjit; Elsherif, Mohamed; Tawfick, Wael; Kavanagh, Edel P; Hynes, Niamh; Sultan, Sherif
Carotid stump syndrome is defined as the persistence of retinal or cerebral ischaemic events with complete occlusion of the ipsilateral internal carotid artery. The aim of this retrospective cases series was to assess the outcomes for patients with carotid stump syndrome managed with surgical intervention. A series of 11 cases of carotid stump syndrome in nine patients presented to our tertiary vascular centre from October 2004 to February 2016. Indications for intervention were amaurosis fugax, transient ischaemic attacks and stroke. In total, 11 procedures were performed on nine patients including carotid angioplasty and stenting or carotid endarterectomy with patching. The mean follow-up period was 56.6 months. One patient suffered a myocardial infarction 30 days, post-operatively, and one patient was lost to follow-up. In the remaining seven patients, there was a complete resolution of symptoms. There were no incidents of death, stroke, cranial nerve injury, wound haematoma or procedural bleeding. Surgical exclusion of carotid stumps combined with dual antiplatelet agents was found to be a safe and effective treatment method for carotid stump syndrome.